An analysis of hedging devices in complaint business letters - Hooi, Chee Mei; Munir Shuib, (Penerbit Universiti Kebangsaan Malaysia, 2014)
Hedging devices are important tools and have been used widely in academic and scientific writing, but their usefulness in business writing has seldom been explored. In a business setting, very few studies have been carried out on hedging in business letters. Some scholars have indicated that the use of hedges is also important in business letters. However, not many business writers are aware of the use and importance of hedging devices in business letters, especially complaint business letters. The aim of the paper is to present findings in the use of hedging devices in complaint business letters among 30 native speakers of English, who have working experience in the business context. The study aims to determine the types and forms of hedging devices that native speakers of English commonly use when writing business letters, as well as, to determine the types and forms of hedging devices that commonly occur in the rhetorical sections (introduction, body, and closure) of business letters. The study employs Hyland‟s model of hedging to identify the forms and types of hedges commonly used by native speakers of English. The findings show that content-oriented hedges are used more frequently in terms of types of hedging devices, while reader pronouns are the forms of hedging devices that are used most frequently in terms of forms of hedging devices in complaint business letters. In all the rhetorical sections of complaint business letters, content-oriented hedges and reader pronouns are commonly used. From the findings, it is clear that hedging is an important aspect of business writing because hedges make a text more reader-friendly since those hedges allow negotiation to occur between the writer and the reader. Hedges also allow the message to be carried across more clearly and precisely.